# Find the value of the expression y ^ 2 + 2y + 3 at y = −1 / 4.

Substitute in the original equation the value of y, which from the condition is -1/4. We get: (-1/4) ^ 2 + 2 * (- 1/4) + 3 = (squaring means the number is multiplied by itself, in the second term we will open the brackets and instead of adding, we get a subtraction) = (-1/4 ) * (- 1/4) -2 * 1/4 + 3 = (in the first term, minus is multiplied by minus and give a plus, when multiplying the numerators are multiplied among themselves, and the denominators among themselves) = 1 / 16-2 / 4 + 3 = (the first two terms are reduced to a common denominator, this is 16, which means we leave the first fraction, and multiply the second by 4) = 1 / 16-8 / 16 + 3 = (1-8) / 16 + 3 = -7 / 16 + 3 = (in order to subtract the fraction from 3, we represent it as 2 integers 16/16 – which is 3. We can also swap the terms for convenience of calculation, since changing the places of the terms will not change the sum) = 2 integers 16/16 – 7 / 16 = 2 integers 9/16.

Answer: 2 point 9/16